2019
DOI: 10.1186/s12871-019-0711-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ketofol versus propofol as an induction agent on ease of laryngeal mask airway insertion conditions and hemodynamic stability in pediatrics: an observational prospective cohort study

Abstract: BackgroundLaryngeal mask airway is a supraglottic airway device which has led to a fundamental change in the management of modern general anesthesia. In the present study; we evaluated the laryngeal mask airway insertion conditions and hemodynamic changes comparing ketamine-propofol mixture (ketofol) with propofol. The study was to compare the ketamine–propofol mixture (ketofol) with propofolon the ease of laryngeal mask airway insertion conditions and hemodynamic effects for induction of general anesthesia.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 22 publications
1
18
1
1
Order By: Relevance
“…Though in terms of mean arterial blood pressure and duration of apnea ketofol was better than propofol. 20 Another study showed results contrary to ours with no significant difference between two groups for jaw relaxation and adverse airway reflexes in elderly patients. 21 Gupta A et al also showed PK (propofol-ketamine) group with least success in n= 12 (40%) patients as compared to 13 (43.33%) patients in Group PF (propofol-fentanyl) and in 26 (86.67%) patients in Group PB (propfol-botarphanol).…”
Section: Discussioncontrasting
confidence: 64%
“…Though in terms of mean arterial blood pressure and duration of apnea ketofol was better than propofol. 20 Another study showed results contrary to ours with no significant difference between two groups for jaw relaxation and adverse airway reflexes in elderly patients. 21 Gupta A et al also showed PK (propofol-ketamine) group with least success in n= 12 (40%) patients as compared to 13 (43.33%) patients in Group PF (propofol-fentanyl) and in 26 (86.67%) patients in Group PB (propfol-botarphanol).…”
Section: Discussioncontrasting
confidence: 64%
“…Recently, Aberra et al, in a study done on 120 pediatric patients aged from 2 to 15 years undergoing elective ophthalmic surgical procedures under general anesthesia using laryngeal mask airway (LMA) to compare the ketamine-propofol mixture (ketofol) with propofol only on the ease of laryngeal mask airway insertion conditions and hemodynamic effects during induction of general anesthesia, found that 54 patients in the ketofol group compared to 52 in the propofol group developed no cough, 6 patients in the ketofol group compared to 7 patients in the propofol group developed a slight cough (coughing which can occur immediately after LMA and subside by itself) and 1 patient in the propofol group developed gross cough (coughing which needs deepening of anesthesia to be relieved ) with no signi cant difference between them. (17) We also, reported that the sedation scores during suction and extubation were signi cantly lower in the KP group compared to the P group. We attributed this good level of sedation during suction and extubation to the analgesic effect of ketamine.…”
Section: Discussionmentioning
confidence: 72%
“…They concluded that Ketofol provided equivalent laryngeal mask airway insertion conditions and it can be used as alternative propofol for LMA insertion. (17) Patients in KP group showed higher level of sedation during the suctioning and extubation procedures when compared to those of the P group. This may be explained by the more sedative and more decreasing of the airway re exes of ketofol during recovery in such short surgical procedures.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations